Curcumin Combined with Aerobic Exercise Improved Liver Function in Rats with Non-alcoholic Fatty Liver Disease - HU Ge, QIN Fei, CAO Jianmin, JI Zhe, ZHOU Qiyun, ZHOU Haitao (Shipin Kexue)
Objective: To explore the effect and mechanism of curcumin combined with aerobic exercise in improving liver function in rats with non-alcoholic fatty liver disease (NAFLD). Methods: Male Sprague Dawley rats were randomly divided into five groups: control, NAFLD model, aerobic exercise intervention, curcumin intervention, and combined intervention with curcumin and aerobic exercise, with 8 rats in each group. Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), total triglyceride (TG), low-density lipoprotein-cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were detected using an automatic biochemistry analyzer. Changes in hepatic histomorphology, lipid deposition and ultrastructure were detected by hematoxylin-eosin, oil red O, and electronic staining. The mRNA and protein expression levels of hepatic adenosine monophosphate-activated protein kinase (AMPK), phosphorylated adenosine monophosphate-activated protein kinase (p-AMPK), mammalian target of rapamycin (mTOR), Beclin-1, sequestosome-1 protein (SQSTM1/p62), microtubule-associated protein 1 light chain 3-I (LC3-I), and LC3-II were detected by real-time quantitative polymerase chain reaction (real-time PCR), immunohistochemistry and Western blot. Results: NAFLD was successfully induced after eight weeks of a high-fat diet. Curcumin and/or aerobic exercise intervention ameliorated liver ultrastructural damage, pathological changes, and lipid deposition in NAFLD rats, decreased serum levels of TC, TG, LDL-C, as well as serum AST and ALT activities, up-regulated the mRNA expression levels of hepatic Beclin1 and LC3-II and the protein expression levels of p-AMPK, Beclin1, and LC3-II, along with the protein expression ratios of p-AMPK/AMPK and LC3-II/LC3-I, and down-regulated the mRNA and protein expression levels of mTOR and p62, thereby enhancing cellular autophagy. Curcumin and aerobic exercise interacted with each other to regulate serum TC and TG levels, ALT and AST activities, hepatic mTOR, Beclin-1, and p62 mRNA expression, p-AMPK, p62, and LC3-II protein expression and the protein expression ratio of LC3-II/LC3-I. Conclusion: Curcumin and/or aerobic exercise intervention could improve liver structure and function in NAFLD rats by moderately enhancing cellular autophagy through the regulation of the AMPK/mTOR signaling pathway. The effect of curcumin combined with aerobic exercise was more pronounced than that of either treatment alone.